Parasite-based screening and proteome profiling reveal orlistat, an FDA-approved drug, as a potential anti trypanosoma brucei agent - Ngai, Mun Hong (2013)
Trypanosoma brucei is a parasite that causes African sleeping sickness in humans and nagana in livestock and is transmitted by the tsetse fly. There is an urgent need for the development of new drugs against African trypanosomiasis due to the lack of vaccines and effective drugs. Orlistat (also called tetrahydrolipstatin or THL) is an FDA-approved antiobesity drug targeting primarily the pancreatic and gastric lipases within the gastrointestinal tract. It shows potential activities against tumors, mycobacteria, and parasites. Herein, we report the synthesis and evaluation of an expanded set of orlistat-like compounds, some of which showed highly potent trypanocidal activities in both the bloodstream form (BSF) and the procyclic form (PCF) of T. brucei. Subsequent in situ parasite-based proteome profiling was carried out to elucidate potential cellular targets of the drug in both forms. Some newly identified targets were further validated by the labeling of recombinantly expressed enzymes in Escherichia coli lysates. Bioimaging experiments with a selected compound were carried out to study the cellular uptake of the drug in T. brucei. Results indicated that orlistat is much more efficiently taken up by the BSF than the PCF of T. brucei and has clear effects on the morphology of mitochondria, glycosomes, and the endoplasmic reticulum in both BSF and PCF cells. These results support specific effects of orlistat on these organelles and correlate well with our in situ proteome profiling. Given the economic challenges of de novo drug development for neglected diseases, we hope that our findings will stimulate further research towards the conversion of orlistat-like compounds into new trypanocidal drugs.